Antimicrobial activity and antibiotic synergy of a biphosphinic ruthenium complex against clinically relevant bacteria. Issue 4 (20th April 2020) - Andrade, Alexandre Lopes; de Vasconcelos, Mayron Alves; Arruda, Francisco Vassiliepe de Sousa; do Nascimento Neto, Luiz Gonzaga; Carvalho, José Marcos da Silveira; Gondim, Ana Claudia Silva; Lopes, Luiz Gonzaga de França; Sousa, Eduardo Henrique Silva; Teixeira, Edson Holanda
Abstract: The aim of this study was to investigate the antibacterial activity, antibiotic-associated synergy, and anti-biofilm activity of the ruthenium complex, cis -[RuCl2 (dppb) (bqdi)] 2+ (RuNN). RuNN exhibited antimicrobial activity against Gram-positive bacteria with minimum inhibitory concentration (MIC) values ranging from 15.6 to 62.5 µg ml −1 and minimum bactericidal concentration (MBC) values ranging from 62.5 to 125 µg ml −1 . A synergistic effect against Staphylococcus spp. was observed when RuNN was combined with ampicillin, and the range of associated fractional inhibitory concentration index (FICI) values was 0.187 to 0.312. A time-kill curve indicated the bactericidal activity of RuNN in the first 1–5 h. In general, RuNN inhibited biofilm formation and disrupted mature biofilms. Furthermore, RuNN altered the cellular morphology of S. aureus biofilms. Further, RuNN did not cause hemolysis of erythrocytes. The results of this study provide evidence that RuNN is a novel therapeutic candidate to treat bacterial infections caused by Staphylococcus biofilms.